2022
DOI: 10.1186/s12912-022-01018-6
|View full text |Cite
|
Sign up to set email alerts
|

Competencies and needs of nurse educators and clinical mentors for teaching in the digital age – a multi-institutional, cross-sectional study

Abstract: Background The impact of technology and digitalization on health care systems will transform the nursing profession worldwide. Nurses need digital competencies to integrate new technology in their professional activities. Nurse educators play a crucial role in promoting the acquisition of digital competences and therefore need to be digitally competent themselves. Research on digital competencies of nursing educators is scarce but suggests lack of digital knowledge and skills and support needs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 43 publications
1
3
0
1
Order By: Relevance
“…The current study findings was supported with [19] who conducted study about" Perceptions of Information Technology in Nursing Education" they found that educational needs regarding of information technology was moderate. Also this study findings was agreed with [20], who conducted study about "Competencies and needs of nurse educators and clinical mentors for teaching in the health information system" found that importance of the health information was moderate.…”
Section: Discussionsupporting
confidence: 89%
“…The current study findings was supported with [19] who conducted study about" Perceptions of Information Technology in Nursing Education" they found that educational needs regarding of information technology was moderate. Also this study findings was agreed with [20], who conducted study about "Competencies and needs of nurse educators and clinical mentors for teaching in the health information system" found that importance of the health information was moderate.…”
Section: Discussionsupporting
confidence: 89%
“…Nurse educators need to enhance their proficiency in utilizing technology effectively because they play a critical role in promoting the acquisition of digital competences among nursing students. Considering that contemporary nurses need digital competencies to integrate new technology into their practice, digital competencies of nursing educators are important but previous studies have suggested lack of digital knowledge and skills among nursing educators [ 20 ]. Nursing faculty should incorporate ICT competencies into the nursing education program.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the digital competencies of educators (e.g. digital teaching strategies, selection of learning material, integrating technology into instruction, learning management, assessment) are considered as critical skills for meaningful and interactive digital oncology training [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%